Analisis Pemahaman Konsep Listrik Dinamis pada Siswa SMAN 8 Palu - Wahyuni Nasir Laratu; Ielda Paramita; Gustina Gustina (Jurnal Kreatif Online, 2022)
This study aims to analyze students' understanding of concepts at SMAN 8 Palu on dynamic electricity. This research is a quasi-experimental research. This research is a qualitative descriptive. The subject in this study is 33 students. The research instrument was in the form of a dynamic electricity material description test based on an indicator of understanding the concept. From the results of data analysis, it was obtained that the criteria for understanding students' concepts included 5 students who were in the high criteria, 9 students in the sufficient criteria, 12 students in the low criteria, and 7 students in the very low criteria. As for the indicator of understanding the concept, it was found that 67.17% restated a concept, 69.09% changed one form of representation to another, 61.69% developed the necessary/sufficient requirements of a concept, 54.21% used and utilized and chose procedures certain activities, and 44.32% clarify concepts in everyday life. The conclusion of this study is that students' understanding of dynamic electricity concepts in SMAN 8 Palu is in the sufficient category.